Evaluation of the occurrence and type of antiretroviral and opportunistic infection medication errors within the inpatient setting - Chiampas TD; Kim H; Badowski M (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Background: Previous data reports inpatient antiretroviral (ARV) and opportunistic infection (OI) medication errors in as many as 86% of patients, with averages ranging from 1.16-2.7 errors/patient. Objective: To determine the occurrence and type of inpatient ARV and OI medication errors at our institution. Methods: A retrospective, observational, electronic medical chart review of patients with HIV/AIDS admitted between February 15, 2011- May 22, 2012 was conducted to assess the occurrence and type of ARV and OI medication errors. Secondary outcomes included assessing each medication with an error and evaluating its potential for a medication error, calculating a medication error rate per patient, evaluating whether a non-formulary (NF) medication impacted the error potential, determining whether a clinical pharmacist on service decreased the medication error rate, and assessing whether patients who experienced an error were more likely to have a longer length of stay (LOS). Analysis included descriptive statistics, averages, and Spearmen rank correlation. Results: There were 344 patients included in this analysis, 132 (38%) experienced 190 medication errors (1.44 errors/patient). An omitted order was the most frequent ARV error and accounted for 30% (n=57) of total errors. There were 166 patients requiring OI medications, 37 patients experienced 39 medication errors. Omitting OI prophylaxis accounted for 31 errors. Only 45 of 190 (24%) errors were corrected prior to discharge. Being prescribed at least 1 NF medication was correlated with increased errors (n=193 patients "on NF medication", p<0.025, r=0.12). Coverage of a service by a clinical pharmacist did not affect the number of errors. Patients experiencing an error had a longer LOS (p=0.02). Conclusions: Errors relating to ARV and OI medications are frequent in HIV-infected inpatients. More errors occurred in patients receiving NF medications. Suggested interventions include formulary revision, education, and training. Dedicated HIV clinicians with adequate training and credentialing may improve the management of this specialized disease state.